MAKNA SEMIOTIK TARI MALUAYA PADA PROSES PEMAKAMAN KAUM BANGSAWAN DI DESA HILIGANOWO KABUPATEN NIAS SELATAN - Daya, Eduar (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
This research is motivated by the lack of documented information about Nias culture, one of which is the maluaya dance. The maluaya dance, which was performed at funeral ceremonies for the nobility, is gradually losing its sustainability. This is because the implementation of the maluaya dance can only be carried out at funerals for the nobility (Si’ulu) and people who are classified as well-off, for the intellectual group (Si’ila) not all can carry it out because apart from looking at the family’s abilities, they also have to fulfill several requirements. . The aim of this research is to determine the cultural semiotic meaning of the maluaya dance, the procedures for its implementation, the equipment and clothing used in the maluaya dance. The approach used in this research is a qualitative approach with descriptive research type. Based on the research results, the maluaya dance has two meanings, namely a discursive meaning and a presentational meaning. The researcher advises readers not only to know about the existence of the maluaya dance culture, but also to know the meaning contained in it and as one of the traditional cultural heritages of Nias, it is an obligation to preserve the culture that has been passed down from generation to generation.